Determinants of SMEs Financial Behavior in Gresik with Financial Literacy as an Intervening Variable - Anita Handayani; Fazlur Rahman Rahawarin; Ery Tri Djatmika Rudijanto; Wahju Wardhana; Puji Handayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Financial Behavior is the ability of a person who is fundamentally able to manage day-to-day financial funds effectively based on planning, budgeting, auditing, managing, controlling, searching, and storing, and aims related to the responsibility for making financial decisions. The purpose of this research is to find out the direct and indirect effects that can affect financial behavior. This study used 150 MSME respondents in Gresik, who were analyzed using the Structural Equation Model (SEM), with the variables used financial attitude, level of education, financial behavior, and financial literacy as intervening variables. The results showed that the variables of education level and financial attitude had an influence on financial literacy and financial behavior, and the financial literacy variable was able to become an intervening variable to influence the level of education on financial behavior, and financial attitudes to financial behavior. In the research that has been done that financial behavior is a very important thing to have concerning how one's attitude and perspective in financial matters, including SMEs, especially those in Gresik. Besides that, the importance of financial literacy is also very much needed because the more a person has a lot of information about finances, it can also affect one's perspective on how money management should be done to reduce the financial risks that must be faced.